ROLE OF AGRICULTURAL INSTITUTIONS OF CHINESE-EASTERN RAILWAY IN THE FORMATION OF THE SOYBEAN COLLECTION AT THE VAVILOV INSTITUTE OF PLANT INDUSTRY AND ITS BREEDING IN THE USSR - I. V. Seferova; M. A. Vishnyakova (Вавиловский журнал генетики и селекции)
In 1920s, agricultural research institutions (experimental stations) working at the CER collected many local Manchurian soybean varieties. The experimental stations tested the collected material and raised new cultivars. More than 3000 soybean accessions were submitted to the Vavilov Institute of Plant Industry. The article describes this material and its significance for breeding in the USSR.